2002
DOI: 10.1152/ajpheart.00789.2001
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Na+/Ca2+exchanger in endothelial NO production and endothelium-dependent relaxation

Abstract: Endothelial nitric oxide (NO) synthase (eNOS) is controlled by Ca(2+)/calmodulin and caveolin-1 in caveolae. It has been recently suggested that Na(+)/Ca(2+) exchanger (NCX), also expressed in endothelial caveolae, is involved in eNOS activation. To investigate the role played by NCX in NO synthesis, we assessed the effects of Na(+) loading (induced by monensin) on rat aortic rings and cultured porcine aortic endothelial cells. Effect of monensin was evaluated by endothelium-dependent relaxation of rat aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
5
41
0
Order By: Relevance
“…We found that KB-R7943 at low concentrations (up to 10 M) did not change ATP-induced Ca 2ϩ transients in MAECs, which is consistent with the finding that KB-R7943 at 1 M did not inhibit EDR (25). In addition, we found that the subtype of NCX in MAECs is NCX1.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that KB-R7943 at low concentrations (up to 10 M) did not change ATP-induced Ca 2ϩ transients in MAECs, which is consistent with the finding that KB-R7943 at 1 M did not inhibit EDR (25). In addition, we found that the subtype of NCX in MAECs is NCX1.…”
Section: Discussionsupporting
confidence: 90%
“…This mechanism may enable endothelial cells to release an appropriate amount of NO by regulating increases in [Ca 2ϩ ] i . On the other hand, as shown in this study, the reverse mode of NCX increases [Ca 2ϩ ] i and evokes EDR in Na ϩ -loaded conditions (6,25,28). In pathophysiological situations such as under oxidative stress, excessive Na ϩ entry via redox-activated cation channels has been observed (2,8).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…These proteins are localised in the plasmalemmal caveolae in close proximity to eNOS and participate in the control of sub-plasmalemmal intracellular Ca 2+ , which is of particular importance for modulation of eNOS activity [34,35]. The high affinity/low capacity PMCA is the principal Ca 2+ removal system in vascular endothelium [36].…”
Section: Additive Effects Of D-glucose and Insulin On Nitric Oxide Fomentioning
confidence: 99%